A218 SODIUM PHOSPHATE IS SUPERIOR TO POLYETHYLENE GLYCOL IN CONSTIPATED PATIENTS UNDERGOING COLONOSCOPY: A SYSTEMATIC REVIEW AND META-ANALYSIS. (15th March 2019) - Dang, J; Moolla, M; Dang, T; Shaw, A; Tian, C; Karmali, S; Sultanian, R
Abstract: Background: We performed a systematic review and meta-analysis to determine the optimal bowel preparation in constipated patients undergoing colonoscopy. Constipation is an important and highly prevalent predictor of inadequate bowel preparation during colonoscopy. In North America, between 2% and 28% of the general population suffer from constipation. Despite the high prevalence of constipation, to our knowledge, no meta-analysis on optimal bowel preparations for constipated patients has been performed. Furthermore, while the literature recognizes constipation as a predictor for poor bowel preparation, specific recommendations regarding the preparation of these patients for colonoscopy remain scarce. Aims: 1. Determine the optimal bowel preparation in chronically constipated patients Methods: A comprehensive search of electronic databases (MEDLINE, EMBASE, SCOPUS, and Web of Science) was performed. Studies were assessed using the following inclusion criteria: adult patients (age ≥ 18 years), randomized controlled trial study design, studies comparing two or more different bowel preparations, studies that included constipated patients, and studies that assessed the effectiveness of the bowel preparation. The primary outcome of interest was the quality of the bowel preparation measured with either validated or non-validated scales. Studies varied in the criteria used to distinguish patients as constipated, therefore, for this review patients were considered constipated based on the method the study authors used to define constipation. Where possible, meta-analysis was performed to compare the percentage of successful bowel preparations amongst constipated patients receiving Polyethylene Glycol (PEG) versus constipated patients receiving Sodium Phosphate (NaP). Results: Preliminary database search yielded 1581 articles after duplicates were removed. After screening of the titles and abstracts using the exclusion criteria, 358 full-text articles were retained. Full text articles were reviewed and eight studies meeting the inclusion criteria were included for qualitative synthesis. Three randomized controlled trials identified a total of 1636 constipated patients, of whom 225 were eligible for meta-analysis. Of those, 107 (47.6%) received NaP and 118 (52.4%) received PEG. The weighted mean age was 57.6 years and weighted sex was 53.5% female. When compared to the PEG cohort, the NaP cohort had a higher likelihood of having a successful bowel preparation (odds ratio [OR] 1.87, CI 1.06 to 3.32, P = 0.003). Conclusions: In chronically constipated patients undergoing colonoscopy, the use of NaP resulted in superior colonic cleanliness when compared to PEG. Barring contraindications, NaP should be used over PEG in constipated patients to improve the quality of bowel preparation. Funding Agencies: None